Face-to-face sun protection training and text messages improve sun protection behaviour in adolescent organ transplant recipients: HIPPOlino feasibility study - Sachse, Michael; Böttcher, Silke; Pape, Lars; Wagner, Gunnar; Mehls, Otto; Klaus, Günter; Laschkewski, Gudrun; Bart, Mareike; Jahn, Ingeborg; Zeeb, Hajo (Acta dermato-venereologica, 2016)
Adolescent organ transplant recipients have an increased risk of developing skin cancer. The aim of this study was to evaluate the technical feasibility and acceptability of short messaging service-based sun protection recommendations for adolescent patients.